Perkembangan Politik dan Kebudayaan Kerajaan Kutai Berdasarkan Prasasti Yupa - Reza Aditia; Rismella Trio Zambulanggi; Intan Oktariani; Hudaidah Hudaidah; Wahyu Rizky Andhifani (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study discusses the political and cultural development of the Kutai Kingdom by placing the Yupa Inscription as the main source in its historical reconstruction. Through a literature review method, this article analyzes historical, archaeological, and epigraphic literature to understand the dynamics of the kingdom in the 4th to 5th centuries AD. The study shows that the geographical environment of the Mahakam River provided strategic conditions for the formation of a centralized power structure and connectivity with international trade networks. Epigraphic data reveals the existence of an organized succession system, a mechanism of legitimization through ritual offerings, and the role of local elites in the early stages before the influence of Indian culture grew stronger. The use of Sanskrit, Pallava script, and Hindu-Shiva religious practices shows the ongoing process of Indianization that wasadapted to the local context. The results of the study confirm that the development of Kutai was the result of interaction between indigenous traditions and foreign elements, thus providing an important basis for the emergence of political, religious, and literacy patterns that later became characteristic of early of the Nusantara.